Analysis of research trends on tax morale in indexed journals in Indonesia - Libran, Muhammad Akbar; Ramadhan, Muhammad Rizky; Syahrin, Alfi; Saputra, Fathur Satria; Purba, Hans Nehemia Natanail; Wijaya, Suparna (WIM Solusi Prima, 2024)
This study aims to analyze the research trends on tax morale in taxation journals indexed in Indonesia from 2019 to 2024. The method used is a systematic literature review by collecting data from various journals accredited by the Science and Technology Index (SINTA). The results show a significant increase in the number of publications discussing tax morale, especially in 2020, influenced by the COVID-19 pandemic. Factors such as trust in the government, social norms, and strict sanctions were found to have a positive impact on tax morale and tax compliance. The study also found that tax morale can be an effective tool for improving tax compliance through a holistic approach, including tax education, tax audits, sanctions, and incentives. This study provides important contributions to the taxation literature by presenting an in-depth analysis of tax morale research trends and their implications for tax policy in Indonesia. These findings are expected to help policymakers design more effective and sustainable taxation strategies.